Optimization and control in the chemical processes - Pulotova Mokhira Rakhmatilloyevna (International Journal of Human Computing Studies, 2020)
Control is a good alternative solution to obtain the desired product yield and still maintain the safety conditions, without changing the system’s configuration or replacing the existent components with new ones. A mathematical model of a thermal cracking coil was developed, based on free radical mechanism and some basic assumptions. In order to predict the coil’s behavior (temperature, product yields and pressure), a simulator for the dynamic process was used. This paper represents a preliminary dynamic behavior study for implementing advanced process control and optimization.